Brasil, 1979-1989 : uma década perdida? - Rostoldo, Jadir Peçanha (2003)
Analyses the transformations of the Brazilian Society, from 1979 to 1989, making reflections that take to a wider comprehension of the country problems. The analysis was done through a multi-disciplinary view, questioning the expression Lost Decade , which the period is usually connected to. Recovers the economic politics from 1955 to 1989. Describes the cultural expressions, social movements and syndicalist movement of the 1980 s, showing their transforming action. Runs over about the redemocratization process, since the politic amnesty until the direct elections for President. Brings the social indicators of the period, including the Human Development Index (HDI) and its relation to the concept of human development. The conclusions show that even there was economic recession, the society had positive achievements in many aspects and the period can be considered as a period of changes and transformations, not lost.